Vanadium-doped LiNbO3 piezoelectric coating with high piezoelectric property and preparation method thereof
By doping vanadium atoms in the LiNbO3 piezoelectric coating and using magnetron sputtering technology, the problem of low piezoelectric constant in the existing technology in the high temperature environment is solved, and the piezoelectric constant and ultrasonic signal strength are significantly improved. Suitable for high temperature application scenarios.
Patent Information
- Application Number
- CN202411650824.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing ultrasonic sensor materials have a low piezoelectric constant in high temperature environments, which is difficult to meet the needs of high temperature application scenarios such as nuclear power plants. In particular, the piezoelectric constant d33 value of LiNbO3 materials is low, which limits its application in high temperature environments.
By doping vanadium atoms into the LiNbO3 piezoelectric coating, vanadium-doped lithium niobate target was designed, and a vanadium-doped LiNbO3 piezoelectric coating was prepared using magnetron sputtering technology, and the doping amount and deposition parameters of vanadium were adjusted to improve the Piezoelectric constant and ultrasonic signal.
The piezoelectric constant d33 and ultrasonic signal strength of the vanadium-doped LiNbO3 piezoelectric coating are significantly improved, which is 2.3 times higher than that of the pure LiNbO3 coating, and the ultrasonic signal strength reaches 10.4 times, and has excellent temperature resistance.
Smart Images

Figure CN119144932A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium niobate coating and sensor, in particular to high voltage electrical performance vanadium-doped LiNbO 3 Preparation technology of piezoelectric coating. Background Art
[0002] The development of ultrasonic sensors that can operate reliably and stably for a long time in high temperature, irradiation and other environments is a prerequisite for online stress monitoring in special application scenarios such as nuclear power plants. Piezoelectric film is the most important component of ultrasonic sensors. The ability of piezoelectric film to transmit ultrasonic waves mainly depends on its piezoelectric constant d 33 The piezoelectric thin film materials used in ultrasonic sensors commonly used in the industrial field mainly include lead zirconate titanate (PZT), zinc oxide (ZnO), aluminum nitride (AlN) and lithium niobate (LiNbO 3 )wait.
[0003] PZT thin film materials have excellent piezoelectric properties and are widely used, but their operating temperature is generally below 200°C, which makes them unsuitable for high-temperature applications in nuclear power plants. ZnO thin film materials are easy to prepare and are mostly used in high-frequency ultrasonic devices, but their piezoelectric constant is low and their operating temperature is relatively low, which cannot meet the high-temperature environment of nuclear reactors above 400°C. For example, Cannata et al. in the United States used a sputtering method to prepare a 100MHz (ZnO) ultrasonic thin film sensor on an aluminum substrate, and the operating temperature is generally below 400°C. AlN thin film materials have become the main choice for high-temperature ultrasonic probes because of their high operating temperature (Curie temperature ~2800°C). Kirk et al. in the United Kingdom used radio frequency sputtering to deposit and prepare high-temperature ultrasonic sensors that can be used for a long time at 600°C on aluminum alloy and low-carbon steel substrates. However, the biggest problem with AlN thin film materials is that their piezoelectric constant is very low (d 33 Value ~7 pC / N), and due to the long propagation distance of ultrasound and material attenuation, the ultrasonic echo signal is weak and difficult to identify, it is difficult to directly apply it to large-sized nuclear power bolts. LiNbO 3 The use temperature of thin film materials is high (1110℃), which can meet the high temperature environment requirements of nuclear power plants. Mohimi, UK, discovered LiNbO 3 The sensor can work for a long time at 600℃. Castilla, a Canadian researcher, found that LiNbO prepared by sol-gel method 3 The application temperature of piezoelectric coating reaches 750℃. Atsushi in the United States prepared single crystal LiNbO with an operating temperature of up to 1000℃ 3 High temperature sensor. But LiNbO 3 The biggest problem is that its piezoelectric constant is very low (d 33 value ~6 pC / N).
[0004] Therefore, for some special high-temperature application environments, how to prepare a thin film coating and a corresponding ultrasonic sensor so that it can meet the high-temperature application scenarios while also having better piezoelectric properties is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The present invention provides a high voltage electrical performance vanadium-doped LiNbO 3 Preparation method of piezoelectric coating. Vanadium-doped LiNbO prepared by the present invention 3 The piezoelectric coating is doped with a certain amount of vanadium to replace part of the niobium, and its piezoelectric constant d 33 Compared with pure lithium niobate crystal and pure LiNbO 3 The coatings are greatly improved; the ultrasonic signal is extremely strong, significantly better than pure LiNbO 3 Coating. It is realized by the following technologies.
[0006] High voltage electrical properties of vanadium-doped LiNbO 3 The method for preparing a piezoelectric coating comprises the following steps:
[0007] Design vanadium-doped lithium niobate targets; clean substrates and magnetron sputtering equipment;
[0008] The vanadium-doped lithium niobate target and substrate are installed in the magnetron sputtering equipment, and the front side of the substrate (i.e., the side for depositing vanadium-doped LiNbO 3 The surface of the piezoelectric coating) and the surface of the vanadium-doped lithium niobate target are arranged in a non-relative state;
[0009] The magnetron sputtering device is evacuated to an ideal vacuum degree and heated to a target temperature;
[0010] Setting environmental parameters to clean the surface of the vanadium-doped lithium niobate target;
[0011] After the vanadium-doped lithium niobate target is cleaned, the front side of the substrate and the surface of the vanadium-doped lithium niobate target are set to be in a relative state and the distance between them is adjusted, and the environmental parameters are set for deposition to obtain vanadium-doped LiNbO 3 Piezoelectric coatings;
[0012] The vanadium-doped lithium niobate target is a lithium niobate target doped with vanadium, and the number of doped vanadium atoms accounts for 1.3-3.9%, that is, the number of vanadium atoms accounts for 1.3-3.9% of the total number of all Li, Nb, V, and O atoms in the target.
[0013] Setting environmental parameters includes introducing Ar gas and O 2 The gas is supplied and the flow rate is controlled, and the RF power and bias voltage are set.
[0014] Vanadium-doped LiNbO prepared by the above-mentioned preparation method provided by the present invention 3 From its microscopic morphology, it can be seen that the piezoelectric coating has a spherical grain morphology and a distinct columnar crystal structure, and does not contain NbO, Nb 2 O 5 、LiNb 3 O 8 Equal impurity phases, close to the ideal form.
[0015] The vanadium-doped LiNbO 3 In the preparation method of the piezoelectric coating, before magnetron sputtering, the target material, substrate and magnetron sputtering equipment need to be cleaned / washed.
[0016] In some embodiments of the present invention, the substrate can be cleaned by using sandpaper with a specific mesh size (e.g., 600-2000 mesh) to polish the surface and back of the substrate. The purpose of polishing the surface and back of the substrate is to remove the natural oxide layer or other impurities on the surface of the substrate, thereby improving the vanadium-doped LiNbO 3 The bonding force between the piezoelectric coating and the substrate improves the conductivity of the substrate and facilitates the substrate to be in a uniform bias environment.
[0017] It is easy to know that the magnetron sputtering equipment includes but is not limited to different components such as a sample holder (i.e. a bracket for placing a substrate), a support seat, and a target fixing ring.
[0018] Therefore, in some implementation cases of the present invention, the cleaning methods for the above-mentioned different components of the magnetron sputtering equipment can be selected as follows: manual polishing with a polishing belt, polishing with an electric grinder, etc., to polish the various components of the magnetron sputtering equipment to improve conductivity; polishing the target fixing ring can prevent impurities and contaminants from being sputtered out during the coating process.
[0019] In some implementation cases of the present invention, the target material is cleaned by loading the target material and the substrate into a magnetron sputtering device. In order to prevent impurities and contaminants on the target material from being sputtered onto the substrate when cleaning the target material, it is necessary to set the target surface and the front side of the substrate in a non-opposite state.
[0020] In some implementation cases of the present invention, the method for preparing the target material provided by the present invention is:
[0021] (1) According to Nb 2 O 5 / Li 2 O=1:1 (molar ratio), and V is added according to the required doping amount. The raw materials are mixed and put into a ball mill for 4-8 hours to form a uniform raw material;
[0022] (2) taking out the sieved material, weighing it and molding it to form a cylindrical target with a diameter of 14.6 cm-19.6 cm and a thickness of 4.1-5.0 mm;
[0023] (3) Annealing treatment was performed at 900°C for 60 min and 1100°C for 2 h in sequence;
[0024] Heat treatment can effectively reduce the hardness of the target material, increase the average grain size of the target material grains, improve the uniformity of the grain size and the long diameter, so that a higher sputtering coating rate can be obtained during coating;
[0025] (4) After natural cooling, the plane and outer circle of the cylindrical target are stripped and bonded to a cylindrical copper backing plate with a diameter of 15 cm-20 cm and a thickness of 3.1-4.0 mm using high-temperature resistant glue, and then cleaned and dried to form the desired vanadium-doped lithium niobate target.
[0026] Through experiments, it was found that as the amount of vanadium doping gradually increased, its longitudinal wave signal and piezoelectric constant increased significantly. When the proportion of vanadium doping atoms was 1.8%, the longitudinal wave signal and piezoelectric constant reached the maximum value; when the proportion of vanadium doping atoms was higher than 1.8%, the longitudinal wave signal and piezoelectric constant gradually decreased; the ideal proportion of vanadium doping atoms was 1.3-3.9%.
[0027] In some embodiments of the present invention, the ideal vacuum degree for evacuating the magnetron sputtering device can be selected to be (1-5)×10 -3 Pa.
[0028] In some implementation cases of the present invention, the target temperature for heating the magnetron sputtering device may be selected to be 100-200° C.;
[0029] Furthermore, in the environmental parameters, the Ar gas and O 2 The volume ratio of the gas flow is (4-6):1, Ar gas and O 2 The total gas flow rate is 0.9-2.0 Pa.
[0030] The vanadium-doped LiNbO 3 In the preparation method of the piezoelectric coating, the strength of the longitudinal wave and shear wave signals can be controlled by adjusting the bias voltage.
[0031] Furthermore, in the setting of environmental parameters, the RF power is 800-900 W and the bias voltage is 7-27 V.
[0032] Furthermore, the distance between the front surface of the substrate and the surface of the vanadium-doped lithium niobate target is 4.5-7 cm.
[0033] Furthermore, the surface cleaning time of the vanadium-doped lithium niobate target is 5-15 min.
[0034] Furthermore, the time for depositing the vanadium-doped lithium niobate target is 8-12 h.
[0035] Furthermore, when the vanadium-doped lithium niobate target and the substrate are installed in the magnetron sputtering equipment, the front side of the substrate and the surface of the vanadium-doped lithium niobate target are set to a non-relative state; or, the back side of the substrate and the surface of the vanadium-doped lithium niobate target are set to a relative state.
[0036] It is easy to know that the above vanadium-doped LiNbO 3 In the preparation method of the piezoelectric coating, the substrate used includes an experimental substrate or an industrial substrate. Among them, the experimental substrate can be selected from a single crystal silicon wafer, a glass wafer, a cemented carbide block, a copper sheet or a stainless steel sheet, which is used to measure the surface morphology, cross-sectional morphology, film thickness, crystal structure, element composition, ultrasonic signal, piezoelectric constant and other information of the coating, providing a reference for industrial applications. Industrial substrates are mainly fasteners such as bolts, nuts, screws or rotor blades, which are used to measure ultrasonic signals, test the piezoelectric properties and high-temperature stability of the coating, and carry out practical applications.
[0037] The present invention also provides a vanadium-doped LiNbO 3 The piezoelectric coating is prepared by any one of the above preparation methods.
[0038] Compared with the prior art, the present invention is beneficial in that:
[0039] 1. Vanadium-doped LiNbO provided by the present invention 3 The piezoelectric coating has obvious spherical grains and columnar crystal structures and does not contain NbO, Nb 2 O 5 、LiNb 3 O 8 The impurity phase and the O / Nb atomic ratio reach 2.9, which is close to the ideal state.
[0040] 2. The present invention designs a lithium niobate target material doped with a specific content of vanadium, so that the deposited LiNbO 3 Vanadium-doped LiNbO is prepared by doping the piezoelectric coating with vanadium. 3 Piezoelectric coating, prepared by vanadium-doped LiNbO 3 Piezoelectric constant d of piezoelectric coating 33 Substantially improved, vanadium-doped LiNbO 3 Piezoelectric constant d of piezoelectric coating 33 It is 2.3 times that of pure lithium niobate crystal and is the purest LiNbO prepared under the same experimental conditions. 3 4.7 times that of piezoelectric coating.
[0041] 3. Vanadium-doped LiNbO provided by the present invention 3 The piezoelectric coating has a very strong ultrasonic signal and is pure LiNbO prepared under the same experimental conditions. 3 10.4 times that of piezoelectric coating.
[0042] 4. Vanadium-doped LiNbO provided by the present invention 3 Piezoelectric coating has excellent temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Pure LiNbO in Example 1 and Comparative Example 1 3 Piezoelectric coating and seven LiNbO with different vanadium doping amounts 3 Ultrasonic and piezoelectric properties test results of piezoelectric coatings.
[0044] Figure 2 The ultrasonic performance test results of Example 2 are shown in FIG.
[0045] Figure 3 The vanadium-doped LiNbO prepared at a bias voltage of 14 V in Example 2 3 Morphology of the piezoelectric coating.
[0046] Figure 4 This is the crystal structure test result of Example 3.
[0047] Figure 5 The ultrasonic performance test results of Example 4 are shown in FIG. DETAILED DESCRIPTION
[0048] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The embodiment of the present invention provides a high voltage electrical performance vanadium-doped LiNbO 3 The preparation method of the piezoelectric coating comprises the following steps:
[0050] (1) Design vanadium-doped lithium niobate targets; clean substrates and magnetron sputtering equipment;
[0051] (2) installing the target and the substrate in the magnetron sputtering device, and setting the front surface of the substrate and the surface of the target in a non-opposing state;
[0052] (3) evacuating the magnetron sputtering device to an ideal vacuum degree and heating it to a target temperature;
[0053] (4) setting environmental parameters to clean the surface of the target material;
[0054] (5) After the target material is cleaned, the front side of the substrate and the surface of the target material are set to be in a relative state and the distance between them is adjusted, and the environmental parameters are set for deposition to obtain vanadium-doped LiNbO 3 Piezoelectric coatings;
[0055] In the above preparation method, the target material is a vanadium-doped lithium niobate target material, and the amount of vanadium doping atoms accounts for 1.3-3.9%;
[0056] Optionally, in the target material, the doping mass of vanadium is 1.8%. When it is higher than 1.8%, its longitudinal wave signal and piezoelectric constant gradually decrease.
[0057] In the above preparation method, setting the environmental parameters includes introducing Ar gas and O 2 The gas is supplied and the flow rate is controlled, and the RF power and bias voltage are set.
[0058] In some implementation cases, the Ar gas and O introduced when setting the environmental parameters 2 The volume ratio of the gas flow is (4-6):1, Ar gas and O 2 The total gas flow rate is 0.9-2.0 Pa.
[0059] Optionally, the introduced Ar gas and O 2 The gas flow volume ratio is 6:1.
[0060] Further optionally, Ar gas and O 2 The total gas flow rate is 1.0 Pa.
[0061] In some implementation cases, the above preparation method evacuates the magnetron sputtering device to a vacuum degree of 5×10 -3 Pa.
[0062] Optionally, the ideal vacuum degree is 4×10 -3 Pa.
[0063] In some implementation cases, the target temperature for heating the magnetron sputtering device in the above preparation method can be selected to be 100-200°C.
[0064] Optionally, the target temperature is 150°C.
[0065] In some implementation cases, the set environmental parameters include a radio frequency power of 800-900 W and a bias voltage of 7-27V.
[0066] In some embodiments, the vanadium-doped LiNbO 3Before the piezoelectric coating is deposited, the distance between the front surface of the substrate and the surface of the target material is adjusted to 4.5-7 cm.
[0067] Optionally, the distance between the front surface of the substrate and the surface of the target material is 4.9 cm.
[0068] In some implementation cases, the target surface cleaning time is 5-15 min.
[0069] In some implementation cases, the target material is deposited for 8-12 hours.
[0070] In some embodiments of the present invention, the designed target material is Nb 2 O 5 , Li 2 O, V, among which Nb 2 O 5 / Li 2 The molar ratio of O is 1:1. The preparation method of the target material is:
[0071] (1) According to Nb 2 O 5 / Li 2 O=1:1 (molar ratio), and V is added according to the required doping amount. The raw materials are mixed and placed in a ball mill for 4-8 hours to form a uniform raw material;
[0072] (2) taking out the sieved material, weighing it and molding it to form a cylindrical target with a diameter of 14.6 cm-19.6 cm and a thickness of 4.1-5.0 mm;
[0073] (3) Annealing treatment is performed at 900°C for 60 min and 1100°C for 2 h in sequence to reduce the hardness of the target material, increase the average grain size of the target material grains, improve the grain size uniformity and aspect ratio, and obtain a higher sputtering coating rate during coating.
[0074] (4) After natural cooling, the plane and outer circle of the cylindrical target are stripped and bonded to a cylindrical copper backing plate with a diameter of 15 cm-20 cm and a thickness of 3.1-4.0 mm using high-temperature resistant glue, and then cleaned and dried to form the desired vanadium-doped lithium niobate target.
[0075] Experimental Example 1: Effect of different vanadium doping contents on vanadium-doped LiNbO 3 The influence of ultrasonic and piezoelectric properties
[0076] The vanadium-doped LiNbO provided in this experimental example 3 The preparation method of the piezoelectric coating is as follows:
[0077] (1) Design 6 targets with different vanadium doping amounts; the target diameter is 14.6 cm and the thickness is 4.1 mm; the copper backing plate diameter is 15 cm and the thickness is 3.1 mm. The vanadium doping amounts (atomic ratio) in the 6 targets are 0.6%, 1.2%, 1.8%, 2.4%, 3.0% and 4.0% respectively.
[0078] Grind the stainless steel substrate: Use 1200-grit sandpaper to grind the front side of the stainless steel substrate (i.e., the side used for depositing vanadium-doped LiNbO 3 The surface of the piezoelectric coating) and the back side.
[0079] The purpose of polishing the front and back surfaces is to remove the natural oxide layer on the substrate surface and increase the vanadium-doped LiNbO 3 The bonding performance of the piezoelectric coating and the substrate, as well as the conductive performance of the substrate, facilitates the substrate to be in a uniform bias environment.
[0080] Grinding belts and electric grinders are used to grind the main components of the magnetron sputtering equipment, including the sample holder, support seat, etc., in order to improve the conductivity; the target retaining ring is polished to prevent impurities and contaminants from being sputtered out during the coating process.
[0081] (2) After the target and substrate are installed in the magnetron sputtering equipment, the back side of the substrate and the surface of the target are arranged to be in a relative state.
[0082] (3) Evacuate the interior of the magnetron sputtering equipment to a vacuum degree of 4×10 -3 Pa, heated to form an environment with a temperature of 150°C.
[0083] (4) Set environmental parameters and introduce Ar and O 2 , Ar / O 2 The volume ratio of Ar and O is 6:1. 2 The total flow rate is 1.0 Pa, the RF power is set to 900 W, and the bias voltage is 7 V; the surface of the target material is cleaned for 10 minutes.
[0084] (5) After cleaning, magnetron sputtering was used to deposit six LiNbO layers with different vanadium doping amounts. 3 Specifically, the front side of the substrate was rotated to face the target surface, the distance between the two was adjusted to 4.9 cm, and Ar and O were introduced. 2 , Ar / O 2 The volume ratio of Ar and O is 6:1. 2 The total flow rate was 1.0 Pa, the RF power was set to 900 W, the bias voltage was 7 V, and the deposition time was 12 h. Six LiNbO with different vanadium doping contents were obtained by deposition. 3 Piezoelectric coating.
[0085] In addition, this test example also selected pure lithium niobate target (without vanadium or any other substance) as a control to prepare pure LiNbO on the surface of stainless steel. 3 The piezoelectric coating,preparation method (deposition steps and equipment parameters, etc.) is the same as the above method.
[0086] The seven vanadium-doped LiNbO prepared by the above preparation method were 3 The piezoelectric coating was tested for element ratio, ultrasonic performance (ultrasonic performance test parameters were: emission voltage 100 V, gain 20 dB) and piezoelectric performance.
[0087] Figure 1 LiNbO with different vanadium doping 3 The test results of ultrasonic and piezoelectric properties of piezoelectric coatings. Figure 1 As shown, pure LiNbO 3 The piezoelectric coating has a longitudinal wave signal of 0.48 V and a piezoelectric constant d 33 3.0 pC / N; LiNbO after vanadium doping 3 The longitudinal wave signal and piezoelectric constant of the piezoelectric coating are significantly improved. When vanadium doping is 1.8%, the O / Nb atomic ratio is 2.89, and its longitudinal wave signal and piezoelectric constant reach the maximum value, which are 5 V and 14 pC / N, respectively, which are pure LiNbO 3 The piezoelectric properties of the coating are 10.4 and 4.7 times of those of the piezoelectric coating. When the vanadium doping content is higher than 1.8%, the longitudinal wave signal and the piezoelectric constant are weakened with the increase of vanadium doping content. When the vanadium doping content is 4.0%, the coating no longer has piezoelectric properties.
[0088] Experimental Example 2: Different bias voltages during deposition for vanadium-doped LiNbO 3 Effect of morphology, structure, ultrasonic properties and piezoelectric properties of piezoelectric coatings
[0089] The vanadium-doped LiNbO provided in this experimental example 3 The preparation method of the piezoelectric coating is basically the same as that of Experimental Example 1, specifically:
[0090] (1) Design a target with a vanadium doping content of 1.8%; the target diameter is 14.6 cm and the thickness is 4.1 mm; the copper backing plate has a diameter of 15 cm and a thickness of 3.1 mm.
[0091] Grind the stainless steel substrate used: Use 1200-grit sandpaper to grind the front and back of the stainless steel substrate.
[0092] The purpose of polishing the front and back surfaces is to remove the natural oxide layer on the substrate surface and increase the vanadium-doped LiNbO 3 The bonding performance of the piezoelectric coating and the substrate, as well as the conductive performance of the substrate, facilitates the substrate to be in a uniform bias environment.
[0093] Grinding belts and electric grinders are used to grind the main components of the magnetron sputtering equipment, including the sample holder, support seat, etc., in order to improve the conductivity; the target retaining ring is polished to prevent impurities and contaminants from being sputtered out during the coating process.
[0094] (2) After the target and substrate are installed in the magnetron sputtering equipment, the back side of the substrate and the surface of the target are arranged to be in a relative state.
[0095] (3) Evacuate the interior of the magnetron sputtering equipment to a vacuum degree of 4×10 -3 Pa, heated to form an environment with a temperature of 150°C.
[0096] (4) Set environmental parameters and introduce Ar and O 2 , Ar / O 2 The volume ratio of Ar and O is 6:1. 2 The total flow rate is 1.0 Pa, the RF power is set to 900 W, and the bias voltage is 7 V; the surface of the target material is cleaned for 10 minutes.
[0097] (5) After cleaning, vanadium-doped LiNbO is deposited using magnetron sputtering and the lithium niobate target designed in step (1). 3 Specifically, the front side of the substrate was rotated to face the target surface, the distance between the two was adjusted to 4.9 cm, and Ar and O were introduced. 2 , Ar / O 2 The volume ratio of Ar and O is 6:1. 2 The total flow rate was 1.0 Pa, the RF power was set to 900 W, the bias voltage was adjusted to 7 V, 14 V and 27 V respectively, and the deposition time was 8 h. Three vanadium-doped LiNbO 3 Piezoelectric coating.
[0098] The three vanadium-doped LiNbO prepared by the above preparation method were 3 The piezoelectric coating was tested for morphology, structure, elements, ultrasonic performance (ultrasonic performance test parameters were: emission voltage 100 V, gain 20 dB) and piezoelectric performance.
[0099] Figure 2 Vanadium-doped LiNbO prepared under three bias voltages 3 Ultrasonic performance test results of piezoelectric coatings; in the figure, LW represents longitudinal wave and SW represents shear wave. Figure 2 As shown in the figure, the signal strength of longitudinal and shear waves can be controlled by adjusting the bias voltage during deposition. When the bias voltage is 7V, the longitudinal wave intensity is higher than the shear wave; and when the bias voltage is 27V, the shear wave intensity is higher than the longitudinal wave.
[0100] The vanadium-doped LiNbO prepared at a bias voltage of 14 V 3 The piezoelectric coating was tested for morphology and structure. The top view (above) and cross-section (below) morphologies are as follows: Figure 3 As shown. It can be seen that vanadium-doped LiNbO 3 The piezoelectric coating still has spherical grain morphology and columnar crystal structure.
[0101] Experimental Example 3: Effect of different vanadium doping contents on vanadium-doped LiNbO 3 Effect of the crystal structure of piezoelectric coatings
[0102] The vanadium-doped LiNbO provided in this experimental example 3 The preparation method of the piezoelectric coating is as follows:
[0103] (1) Four targets with different vanadium doping amounts were designed; the target diameter was 14.6 cm and the thickness was 4.1 mm; the copper backing plate diameter was 15 cm and the thickness was 3.1 mm. The vanadium doping amounts (atomic ratio) in the four targets were 1.2%, 1.8%, 3.0% and 4.0% respectively.
[0104] Grind the stainless steel substrate: Use 1200-grit sandpaper to grind the front side of the stainless steel substrate (i.e., the side used for depositing LiNbO 3 The surface of the piezoelectric coating) and the back side.
[0105] The purpose of polishing the front and back surfaces is to remove the natural oxide layer on the substrate surface and increase the vanadium-doped LiNbO 3 The bonding performance of the piezoelectric coating and the substrate, as well as the conductive performance of the substrate, facilitates the substrate to be in a uniform bias environment.
[0106] Grinding belts and electric grinders are used to grind the main components of the magnetron sputtering equipment, including the sample holder, support seat, etc., in order to improve the conductivity; the target retaining ring is polished to prevent impurities and contaminants from being sputtered out during the coating process.
[0107] (2) After the target and substrate are installed in the magnetron sputtering equipment, the back side of the substrate and the surface of the target are arranged to be in a relative state.
[0108] (3) Evacuate the interior of the magnetron sputtering equipment to a vacuum degree of 4×10 -3 Pa, heated to form an environment with a temperature of 150°C.
[0109] (4) Set environmental parameters and introduce Ar and O 2 , Ar / O 2 The volume ratio of Ar and O is 6:1. 2The total flow rate is 1.0 Pa, the RF power is set to 900 W, and the bias voltage is 7 V; the surface of the target material is cleaned for 10 min.
[0110] (5) After cleaning, four LiNbO layers with different vanadium doping amounts were deposited by magnetron sputtering. 3 Specifically, the front side of the substrate was rotated to face the target surface, the distance between the two was adjusted to 4.9 cm, and Ar and O were introduced. 2 , Ar / O 2 The volume ratio of Ar and O is 6:1. 2 The total flow rate was 1.0 Pa, the RF power was set to 900 W, the bias voltage was 7 V, and the deposition time was 8 h. Four LiNbO with different vanadium doping contents were obtained by deposition. 3 Piezoelectric coating.
[0111] Four LiNbO with different vanadium doping 3 Piezoelectric coatings for crystal structure testing
[0112] Test results such as Figure 4 As shown in the figure, it can be seen that when the atomic amount of vanadium doping is 1.8%, 3.0% and 4.0%, the coating does not contain NbO, Nb 2 O 5 、LiNb 3 O 8 When the vanadium doping amount is 1.8%, the coating has the strongest LiNbO 3 (116) diffraction peak; as the doping amount increases further, LiNbO 3 (116) diffraction peak gradually weakened; when the doping amount was 1.2%, LiNb appeared at 46.2° and 49.2°. 3 O 8 The diffraction peaks of LiNbO 3 The (116) diffraction peak weakened, indicating that the introduction of a certain amount of vanadium doping can effectively weaken the NbO and Nb 2 O 5 、LiNb 3 O 8 The formation of impurity phases.
[0113] Experimental Example 4: Effect of high temperature on vanadium-doped LiNbO 3 Effect of piezoelectric coating on ultrasonic performance
[0114] The vanadium-doped LiNbO provided in this experimental example 3 The preparation method of the piezoelectric coating is basically the same as that of Experimental Example 1, specifically:
[0115] (1) Design a target with a vanadium doping content of 1.8%; the target diameter is 14.6 cm and the thickness is 4.1 mm; the copper backing plate has a diameter of 15 cm and a thickness of 3.1 mm.
[0116] The Ti10Al4V alloy bolts (M8×35 mm) used were polished: the end face and bottom face of the bolts were polished with 1200-grit sandpaper.
[0117] The purpose of grinding the end face and bottom face is to remove the natural oxide layer on the surface of the bolt and improve the vanadium-doped LiNbO 3 The combination of the piezoelectric coating and the bolt, as well as the electrical conductivity of the bolt, allows the bolt to be in a uniform bias environment.
[0118] Grinding belts and electric grinders are used to grind the main components of the magnetron sputtering equipment, including the sample holder, support seat, etc., in order to improve the conductivity; the target retaining ring is polished to prevent impurities and contaminants from being sputtered out during the coating process.
[0119] (2) After the target material and the bolt are installed in the magnetron sputtering equipment, the end surface of the bolt and the surface of the target material are arranged to be in a relative state.
[0120] (3) Evacuate the interior of the magnetron sputtering equipment to a vacuum degree of 4×10 -3 Pa, heated to form an environment with a temperature of 150°C.
[0121] (4) Set environmental parameters and introduce Ar and O 2 , Ar / O 2 The volume ratio of Ar and O is 6:1. 2 The total flow rate is 1.0 Pa, the RF power is set to 900 W, and the bias voltage is 7 V; the surface of the target material is cleaned for 10 minutes.
[0122] (5) After cleaning, vanadium-doped LiNbO is deposited using magnetron sputtering and the lithium niobate target designed in step (1). 3 Specifically, the end face of the bolt was rotated to face the target surface, the distance between the two was adjusted to 4.9 cm, and Ar and O were introduced. 2 , Ar / O 2 The volume ratio of Ar and O is 6:1. 2 The total flow rate was 1.0 Pa, the RF power was set to 900 W, the bias voltage was 27 V, and the deposition time was 9 h. Vanadium-doped LiNbO was obtained by deposition. 3 Piezoelectric coating.
[0123] (6) The vanadium-doped LiNbO prepared by the above preparation method 3The piezoelectric coating was placed in a high-temperature annealing furnace, and the ultrasonic performance (ultrasonic performance test parameters were: transmitting voltage 100 V, gain 20 dB) was tested in real time under high temperature environment to obtain ultrasonic signal curves at 30°C, 300°C, 500°C, and 700°C.
[0124] In addition, this test example also selected pure lithium niobate target (not doped with vanadium or any other substances) as a control, and prepared pure LiNbO on the end face of Ti10Al4V alloy bolt (M8×35 mm). 3 The piezoelectric coating,preparation method (deposition steps and equipment parameters, etc.) is the same as the above method, and the ultrasonic longitudinal wave signal,measured at room temperature is 0.05V and the ultrasonic shear wave signal is 0.1V (ultrasonic performance test parameters are:,transmitting voltage 100 V, gain 20 dB).
[0125] Figure 5 Vanadium-doped LiNbO prepared in Experimental Example 4 3 High-temperature online ultrasonic performance test results of piezoelectric coatings; in the figure, LW represents longitudinal wave and SW represents shear wave. It can be seen that vanadium-doped LiNbO with excellent ultrasonic performance can also be deposited on the end face of Ti10Al4V alloy bolts. 3 Piezoelectric coating, at room temperature, the ultrasonic longitudinal wave signal is 0.23V, and the ultrasonic shear wave signal is 0.7V, which are pure LiNbO 3 The vanadium-doped LiNbO 3 Piezoelectric coating has excellent temperature resistance.
[0126] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for preparing a vanadium-doped LiNbO3 piezoelectric coating with high piezoelectric performance, characterized in that: The following steps are involved: Design of vanadium-doped lithium niobate targets; Cleaning substrates and magnetron sputtering equipment; Installing the vanadium-doped lithium niobate target and the substrate in the magnetron sputtering device, and setting the front surface of the substrate and the surface of the vanadium-doped lithium niobate target in a non-opposite state; The magnetron sputtering device is evacuated to an ideal vacuum degree and heated to a target temperature; Setting environmental parameters to clean the surface of the vanadium-doped lithium niobate target; After the vanadium-doped lithium niobate target is cleaned, the front side of the substrate and the surface of the vanadium-doped lithium niobate target are arranged to be in a relative state and the distance between them is adjusted, and environmental parameters are set for deposition to obtain a vanadium-doped LiNbO3 piezoelectric coating; The vanadium-doped lithium niobate target is a lithium niobate target doped with vanadium, and the amount of vanadium doping atoms accounts for 1.3-3.9%; Setting the environmental parameters includes introducing Ar gas and O2 gas and controlling the inflow flow rate, setting the RF power and bias voltage.
2. The method for preparing the high-voltage electric performance vanadium-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: The ideal vacuum degree is (1-5)×10 -3 Pa.
3. The method for preparing the high-voltage electric performance vanadium-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: The target temperature for heating the magnetron sputtering device may be selected to be 100-200°C.
4. The method for preparing the high-voltage electric performance vanadium-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: In setting the environmental parameters, the flow volume ratio of the introduced Ar gas and O2 gas is (4-6):1, and the total flow rate of Ar gas and O2 gas is 0.9-2.0 Pa.
5. The method for preparing the high-voltage electric performance vanadium-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: In the environmental parameter settings, the RF power is 800-900 W and the bias voltage is 7-27 V.
6. The method for preparing the high-voltage electric performance vanadium-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: The distance between the front side of the substrate and the surface of the vanadium-doped lithium niobate target is 4.5-7 cm.
7. The method for preparing the high-voltage electric performance vanadium-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: The deposition time of vanadium-doped LiNbO3 piezoelectric coating is 8-12 h.
8. The method for preparing the high-voltage electric performance vanadium-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: When the vanadium-doped lithium niobate target and the substrate are installed in the magnetron sputtering equipment, the front side of the substrate and the surface of the vanadium-doped lithium niobate target are set in a non-relative state; or, the back side of the substrate and the surface of the vanadium-doped lithium niobate target are set in a relative state.
9. A vanadium-doped LiNbO3 piezoelectric coating prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Vanadium-doped lithium niobate crystals
CN102296365A
Epitaxial-orientation lithium niobate film based on Pt substrate and growth method thereof
CN108441824A
Doped lithium niobate target material and preparation method and application thereof
CN116425538A
Lithium niobate piezoelectric coating with adjustable and controllable longitudinal and transverse sound waves as well as preparation method and application of lithium niobate piezoelectric coating
CN117467955A
Thermal poling method, piezoelectric film and manufacturing method of same, thermal poling apparatus, and inspection method of piezoelectric property
US20150188031A1
Cited By
High-density LiNbO3 target material, preparation method, piezoelectric coating and application thereof
CN120398537A
High-density LiNbO3 target material, preparation method, piezoelectric coating and application thereof
CN120398537B
Ultra-flat multi-waveform high-V-doped LiNbO3 film sensor and preparation method thereof
CN121137539A
